Mapping strategies, components, and theories used in health education and physical activity interventions to prevent cardiovascular diseases in adults living with HIV: A scoping review protocol - Micah Mutuna Simpamba; Brian Chanda Chiluba; Yvonne Colgrove; Mercy Wamunyima; Esther Munalula-Nkandu (PLoS ONE, 2025)
Introduction Cardiovascular diseases (CVDs) have become the most significant contributor to non-HIV/AIDS-related deaths in people living with HIV (PLWH). The increased risk for CVDs in PLWH is attributed to a combination of traditional risk factors, the effects of chronic inflammation, and antiretroviral therapy-related metabolic changes. Objective The main objective of this scoping review is to systematically map and summarize evidence on the strategies, components, and theories used in health education and physical activity interventions to prevent cardiovascular diseases in PLWH. Inclusion criteria Peer-reviewed publications including relevant grey literature published in English will be included. The literature will focus on health education and physical activity interventions for people living with HIV, at risk of CVDs, aged between 18 years to 65 years. The literature publication will range between 2000 and June, 30th 2025, and intervention studies will include diverse research designs and literature sources from a broad array of settings including healthcare and community settings. Methods Electronic databases to be searched will include PubMed, Scopus, CINAHL, and Embase, as well as grey literature such as Google Scholar, WHO Digital Publications (IRIS), and Proquest Thesis and Dissertation Global. A three-step process of screening consisting of titles/abstracts screening, full article screening, and manual search for references from identified articles will be conducted by two independent reviewers. In case of any discrepancies or disagreements, a third reviewer will be called upon to address the controversy. A data extraction form will be adapted from the Joanne Briggs Institute (JBI) standardized data extraction tool and key findings will be presented in tabular or diagram format followed by a narrative summary. Reporting of the scoping review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist. Review protocol registration The scoping review protocol is registered with Open Science Framework (https://osf.io/4wfkh/).